2014
DOI: 10.1038/srep04417
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Autophagy in Antitumor Activity of Folate-appended Methyl-β-cyclodextrin

Abstract: Autophagy, the major lysosomal pathway for recycling intracellular components including organelles, is emerging as a key process regulating tumorigenesis and cancer therapy. Most recently, we newly synthesized folate-appended methyl-β-cyclodextrin (FA-M-β-CyD), and demonstrated the potential of FA-M-β-CyD as a new antitumor drug. In this study, we investigated whether anticancer activity of FA-M-β-CyD in folate receptor-α (FR-α)-positive tumor cells is involved in autophagy. In contrast to methyl-β-cyclodextri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
0
27
0
Order By: Relevance
“…In addition, FA-M-β-CyD elicited the formation of autophagic vacuoles. 16 Taken together, these results indicate that FR-α-expressing cell-selective cytotoxic activity of FA-M-β-CyD could be mediated by the regulation of autophagy, rather than the induction of apoptosis. However, the mechanism of autophagy induction by FA-M-β-CyD remains unclear.…”
Section: Introductionmentioning
confidence: 63%
See 2 more Smart Citations
“…In addition, FA-M-β-CyD elicited the formation of autophagic vacuoles. 16 Taken together, these results indicate that FR-α-expressing cell-selective cytotoxic activity of FA-M-β-CyD could be mediated by the regulation of autophagy, rather than the induction of apoptosis. However, the mechanism of autophagy induction by FA-M-β-CyD remains unclear.…”
Section: Introductionmentioning
confidence: 63%
“…16 However, in the previous study, the autophagosomes were just detected by Cyto-ID, a LC-3 detector in cells. Meanwhile, in this study, we used Mtphagy Dye, a mitophagy-specific detection kit commercialized most recently by Dojindo Molecular Technologies, Inc., namely, Mtphagy Dye, which accumulates in intact mitochondria, is immobilized …”
Section: Induction Of Mitophagy By Fa-m-β-cydmentioning
confidence: 99%
See 1 more Smart Citation
“…Most interestingly, FA-M-β-CyD inducted autophagy-mediated antitumor effect, not apoptosis. 68) These data suggest that FA-M-β-CyD has potential as a unique antitumor API.…”
Section: Folate-appended Methyl-β-cydmentioning
confidence: 87%
“…35) Previously, we reported that FA-M-β-CyD induced autophagic cell death in KB cells, rather than apoptotic cell death. 36) However, it is still obscure whether FA-M-β-CyD induces autophagy in melanoma cells. Therefore, we next examined whether autophagosome formation in Ihara cells is elicited by FA-M-β-CyD, using Cyto-ID ® Autophagy Detection Kit, which detects autophagic vacuoles in cells.…”
Section: Fig 2 Cellular Association Of Tritc-fa-m-β-cyd In Ihara Cellsmentioning
confidence: 99%